Social Capital of Rice Farmers in Waihatu Village, Kairatu Barat Subdistrict, West Seram Regency - Safiteri, Puput; Koritelu, Paulus; Litaay, Simona Christina Henderika; Leiwakabessy, Jefry E. M. (LPPM Institut Pendidikan Nusantara Global, 2025)
The role of social capital in the agricultural sector, especially in rice production, is crucial as it serves not only as a foundation for national food security but also as a driving force for the rural economy. In Waihatu Village, West Kairatu District, West Seram Regency, rice farmers encounter several obstacles, including limited access to modern technology, market information, and the impacts of climate change, all of which affect crop productivity. This descriptive qualitative study aims to examine the effectiveness of social capital in supporting farmers' productive activities. The research took place in Waihatu Village and involved data collection through in-depth interviews, observations, and documentation. The findings reveal that social capital is already embedded in the interactions between rice farmers and buyers, demonstrating its positive effect on increasing farmer productivity. Key elements of social capital—trust, social networks, and social norms—play a significant role in enhancing agricultural output. Trust among farmers fosters cooperation and mutual assistance, especially in the exchange of knowledge about improved farming techniques. Social networks support the distribution of agricultural products, improve access to business capital, and strengthen ties between farmers and buyers. Additionally, the presence of social norms helps to establish work discipline, promote collaboration, and maintain social cohesion. Importantly, the ethnic diversity in Waihatu Village is not seen as a barrier but rather as a source of shared experiences and innovation in farming practices.